Introduction to telecommunications network engineering - Anttalainen, Tarmo (Artech House telecommunications library., 2003)
Whether you are an executive or sales manager in a networking company, a data communications engineer, or a telecommunications professional, you must have a thorough working knowledge of the ever growing and interrelated array of telecom and data communications technologies. From protocols and operation of the Internet (IP, TCP, HTTP ...) and its access systems such as ADSL, and GSM ... to the basics of transmission and switching, this newly revised resource delivers an up-to-date introduction to a broad range of networking technologies, clearly explaining the networking essentials you need to know to be a successful networking professional. Moreover, the book explores the future developments in optical, wireless and digital broadcast communications.